2022-RA-1078-ESGO Service evaluation of women with stage 1b vulval cancer who underwent groin sentinel lymph node biopsy: The South East Wales Gynaecological Oncology Centre (SEWGOC) experience. (20th October 2022) - Zeinah, Hassan; Tryczynska, Monica; Jones, Sadie; Rzyska, Ewelina; Lim, Kenneth; Howells, Robert; Sharma, Aarti
Abstract : Introduction/Background: The current standard of care for vulval cancer patients with pre-operative stage Ib involves removal of the lesion and assessment of the groin nodes by either performing groins sentinel lymph node biopsy (SLNB) where possible or full groin nodes dissection (GND). For SLNB to be performed, the preoperative cancer stage should be ideally 1B, macroscopic vulval lesion ≤ 4cms/single lesion, not involving any midline structures. The aim of this project is to evaluate the outcomes in women with stage Ib vulval cancer who SLNB as part of their vulval cancer treatment. Methodology: Retrospective review of electronic medical records for all women who underwent SLNB from 1st January 2018 to 31st December 2021 at the South East Wales Gynaecological Oncology Centre (SEWGOC) Results: Thirty-two patients were identified in this time period with stage Ib vulval cancer (as per preoperative biopsy and/or imaging) and were planned to have SLNB. Thirty-one patients underwent successful SLNB. Nine patients (Twenty nine percent) of those who underwent SLNB were found to have metastasis within sentinel lymph node and therefore were upstaged to stage III postoperatively. Those patients were then managed with either full groin node dissection, radiotherapy or both. None of the patients with negative sentinel lymph nodes had a recurrence in the inguinal lymph nodes during the follow up period. Conclusion: Approximately 30% of our preoperative stage 1b vulval cancer were upstaged to stage 3 due to metastatic disease in the SLNB. This service evaluation shows that SLNB is effective method in treatment of early stage vulval cancer. We were able to avoid full groin node dissection with its associated morbidity in almost 70% of our patients and also identify women who were not stage 1b and needed further treatment in the form of further GND with or without radiotherapy.